Radiation versus paclitaxel chemo radiation in the treatment of locally advanced carcinoma of cervix - Sujindra, Elamurugan; Chaturvedula, Latla (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Cervical cancer is the most common malignancy among women. Incomplete local control and the appearance of distant disease herald poor survival. Concurrent chemo radiation is recently developing as the preferred modality of treatment. The objective of this study was to compare the effectiveness of concurrent Paclitaxel chemo radiation to that of only radiation in treatment of patients with locally advanced squamous cell cervical cancer. Methods: The study was carried out at JIPMER, Puducherry from October 2005 to October 2010. There were two groups with 25 patients each. Group 1 received only radiation - 4860 cGy EBRT daily in five fractions per week for a total of 27 fractions followed by HDR brachytherapy. Group 2 received 50 mg/m2 of Paclitaxel on all Mondays followed by concurrent radiotherapy. Patients were assessed at 6 months and 1 year after completion of treatment. In October 2010 they were all examined to calculate four year survival and disease free survival rate. Results: A total of 48 patients were analyzed. Complete response rate was 56% in group 1 and 72% in group 2. At the end of four years survival and disease free survival rate in group 1 was 57.9% and 31.6% and in group 2 was 57.1% and 33.3% respectively. Conclusions: Concurrent chemo radiation with Paclitaxel gives promising results and is more effective method than treatment with only radiation.